2007
DOI: 10.3892/or.17.5.1141
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of 211At labeled HER-2 binding affibody molecules in mice

Abstract: Abstract. The size of affibody molecules makes them suitable as targeting agents for targeted radiotherapy with the ·-emitter 211 At, since their biokinetic properties match the short physical half-live of 211 At. In this study, the potential for this approach was investigated in vivo. Two different HER-2 binding affibody molecules were radiolabeled with 211 At using both the linker PAB (N-succinimidyl-para-astatobenzoate) and a decaborate-based linker, and the biodistribution in tumorbearing nude mice was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…Many other radiohalogens ( 125 I, 76/77/82 Br, and 211 At) and radiometals ( 99m Tc, 111/114m In, 90 Y, 177 Lu, and 68 Ga) have been used to label Affibody molecules (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Our data are generally consistent with the findings reported in these published studies.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Many other radiohalogens ( 125 I, 76/77/82 Br, and 211 At) and radiometals ( 99m Tc, 111/114m In, 90 Y, 177 Lu, and 68 Ga) have been used to label Affibody molecules (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Our data are generally consistent with the findings reported in these published studies.…”
Section: Discussionsupporting
confidence: 83%
“…Over the last decade, noninvasive molecular imaging of HER2 expression with various imaging modalities has been extensively studied; these modalities include radionuclide imaging with PET and SPECT (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), MRI (16), and optical imaging (17,18). PET imaging of HER2 (HER2 PET) is particularly useful because of its high sensitivity, high spatial resolution, strong quantification ability, and great potential for translation to clinical applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our first study was a comparison of the often used 211 At-labeling reagent, N-succinimidyl meta -[ 211 At]astatobenzoate, [ 211 At] 2b 20, 21 with a maleimido- closo -decaborate(2-) derivative, 4 , that had been prepared for conjugation with sulfhydryl groups on Fab́ 5 and engineered mAb fragments containing a cysteine residue. 22 That study demonstrated that higher in vivo stability was obtained, but more importantly, 211 At-labeling yields were much higher and the labeling process was much simpler when using the closo -decaborate(2-) mAb conjugate, 5a , than obtained in the two-step conjugation procedure required for use of [ 211 At] 2b . 4 In a subsequent study in mice directly comparing 211 At-labeled anti-CD45 mAb (30F11 conjugated with 4 ) and 213 Bi-labeled anti-CD45 mAb (30F11 conjugated with CHX-A”-DTPA), it was noted that tissue distributions and therapeutic outcomes were similar.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated as a molecular target for therapeutic intervention, a prognostic indicator of patient survival, and as a predictive marker of response to antineoplastic therapy [68]. Numerous radionuclides including 18 F [911], 99m Tc [1215], 111 In [16–19], 90 Y [20], 177 Lu [20, 21], 68 Ga [22], 125 I [14, 2325], 76/77/82 Br [26], and 211 At [27] have been used to label the anti-HER2 Affibody molecules for tumor imaging or radiotherapy. These studies have clearly demonstrated that Affibody molecules are a promising new class of cancer targeting ligands and worthy of further investigation for developing probes for different tumor targets.…”
Section: Introductionmentioning
confidence: 99%